2003
DOI: 10.1063/1.1567035
|View full text |Cite
|
Sign up to set email alerts
|

Solid immersion lens-enhanced nano-photoluminescence: Principle and applications

Abstract: We demonstrate the combination of a hemispherical solid immersion lens with a microphotoluminescence set-up. Two advantages introduced by the SIL, an improved resolution of 0.4 times the wavelength in vacuum and a 5 times enhancement of the collection efficiency, make it an ideal system for spatially resolved spectroscopy applications. The influence of the air gap between the SIL and the sample surface is investigated in detail. We confirm the tolerance of the set-up to an air gap of several micrometers. Such … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…The sample is mounted on the cold finger of a helium flux cryostat keeping the QDs at about 5K for all the experiments described here. A microscope objective (numerical aperture of 0.4) and a high refractive index (n = 2.16) hemispherical solid immersion lens (SIL) [14] are used to collect the single dot emission efficiently. The 488nm (2.541eV) line of a cw argon laser is sent through the same optics for the excitation.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…The sample is mounted on the cold finger of a helium flux cryostat keeping the QDs at about 5K for all the experiments described here. A microscope objective (numerical aperture of 0.4) and a high refractive index (n = 2.16) hemispherical solid immersion lens (SIL) [14] are used to collect the single dot emission efficiently. The 488nm (2.541eV) line of a cw argon laser is sent through the same optics for the excitation.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Our experimental setup is a far-field nano-PL system based on a confocal microscope [3]. Introducing additionally a solid immersion lens, which is adhesively attached to the sample surface, we achieve a spot size of the exciting laser of 200 nm HWHM.…”
Section: Methodsmentioning
confidence: 99%
“…On first sight scanning nearfield optical microscopy (SNOM) appears to be the method of choice [1,2]. But, since SNOM requires rather elaborate experimental facilities, confocal microscopy enhanced by the introduction of solid immersion lenses (SILs) turned out to be a most efficient and easy to handle alternative [3,4]. The latter method can have a spatial resolution down to 200 nm in terms of the half-width at halfmaximum (HWHM) of the focused laser spot.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years SIL-based microscopy has been used to investigate the optical properties of semiconductor quantum wells [2] and quantum dots [3][4][5]. It has been shown that the numerical aperture of 2 can be achieved when the refraction index of the SIL is very high (GaP 3.5) and closely matches that of the studied sample.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the numerical aperture of 2 can be achieved when the refraction index of the SIL is very high (GaP 3.5) and closely matches that of the studied sample. One of the critical issues related to this technique concerns the presence of the air gap between the surface of the SIL and the epitaxially grown sample [3].…”
Section: Introductionmentioning
confidence: 99%